A comparative evaluation of NB30, NB54 and PTC124 in translational read-through efficacy for treatment of an USH1C nonsense mutation - Goldmann, Tobias (WILEY-VCH Verlag, 2012)
Translational read-through-inducing drugs (TRIDs) promote read-through of nonsense mutations, placing them in the spotlight of current gene-based therapeutic research. Here, we compare for the first time the relative efficacies of new-generation aminoglycosides NB30, NB54 and the chemical compound PTC124 on retinal toxicity and read-through efficacy of a nonsense mutation in the USH1C gene, which encodes the scaffold protein harmonin. This mutation causes the human Usher syndrome, the most common form of inherited deaf-blindness. We quantify read-through efficacy of the TRIDs in cell culture and show the restoration of harmonin function. We do not observe significant differences in the read-through efficacy of the TRIDs in retinal cultures; however, we show an excellent biocompatibility in retinal cultures with read-through versus toxicity evidently superior for NB54 and PTC124. In addition, in vivo administration of NB54 and PTC124 induced recovery of the full-length harmonin a1 with the same efficacy. The high biocompatibilities combined with the sustained read-through efficacies of these drugs emphasize the potential of NB54 and PTC124 in treating nonsense mutation-based retinal disorders.